Exosomes from Adipose-Derived Mesenchymal Stromal Cells Prevent Medication-Related Osteonecrosis of the Jaw by Inhibiting Macrophage M1 Polarization and Pyroptosis - Zheng Y; Wang X; He Y; Chen S; He L; Zhang Y (International Journal of Nanomedicine)
Yi Zheng,1,2 Xinyu Wang,1 Yang He,1 Shuo Chen,1 Linhai He,1,3,* Yi Zhang1,* 1Department of Oral and Maxillofacial Surgery, Peking University School and Hospital of Stomatology, Beijing, 100081, People’s Republic of China; 2Department of Stomatology, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, People’s Republic of China; 3First Clinical Division, Peking University School and Hospital of Stomatology, Beijing, 100081, People’s Republic of China*These authors contributed equally to this workCorrespondence: Linhai He; Yi Zhang, Email helinhai07@126.com; zhangyi2000@263.netPurpose: Exosomes from mesenchymal stromal cells (MSCs) can prevent the development of medication-related osteonecrosis of the jaw (MRONJ) by promoting tooth socket wound healing; however, the exact mechanism remains to be clarified. In this study, our aim was to explore the mechanisms of exosomes derived from adipose-derived mesenchymal stromal cells (ADSCs) in preventing MRONJ by focusing on macrophage M1 polarization and pyroptosis.Methods: The MRONJ model was established by the administration of zoledronate and tooth extraction. Exosomes isolated from the supernatant of ADSCs were mixed with hydrogel and locally injected into the extraction site after tooth extraction. Stereoscope observations, micro computed tomography (microCT), and histological analysis were used to assess tooth socket wound healing.Results: The results showed that exosomes could effectively avoid MRONJ via accelerating gingival wound healing and tooth socket bone regeneration. Mechanistically, zoledronate triggered the NF-κB signaling pathway and promoted p65 transferring into the nucleus in macrophages, resulting in macrophage M1 polarization and pyroptosis-mediated tissue inflammation, while exosomes could reduce macrophage pyroptosis and pro-inflammation cytokines release by suppressing the NF-κB/NLRP3/IL-1β axis. Additionally, IL-1RA derived from exosomes plays a key role in preventing MRONJ. Pyroptosis-related and inflammatory-related processes were upregulated in MRONJ patients further confirmed by assessing MRONJ gingival samples and healthy gingival tissues.Conclusion: ADSCs-derived exosomes could effectively promote tooth socket healing and prevent MRONJ by inhibiting M1 macrophage activation and pyroptosis by blocking the NF-κB/NLRP3/IL-1β axis.Keywords: Medication-related osteonecrosis of the jaw, exosomes, macrophage M1 polarization and pyroptosis, primary wound healing, NF-κB/NLRP3/IL-1β axis